Holding-Together Regionalism: Twenty Years of Post-Soviet Integration - Libman, Alexander; Vinokurov, E.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
An in-depth analysis of one of the most important and complex issues of the post-Soviet era, namely the (re-)integration of this highly interconnected region. The book considers the evolution of 'holding-together' groups since the collapse of the Soviet Union in 1991, looking at intergovernmental interaction and informal economic and social ties.
Keywords: Economic policy; Regional economics; Spatial economics; Political economy; Macroeconomics; Economic history; Regionalism; Economic Policy; Regional/Spatial Science; International Political Economy; Macroeconomics/Monetary Economics//Financial Economics; Economic History; Regionalism